Determining factors for economic upgrading in the global value chain of the blackberry fruit cluster in Los Reyes, Michoacán, Mexico (Agro Productividad, 2025)
Objective: to measure the impact of variables such as innovation, public policy, dependency and inequalities among actors and at the level of organization so that the producer of blackberry fruit (Rubus sp.) can achieve upgrading in the global value chain (GVC).Design/ Methodology/ Approach: a partial least squares technique was used for measurement, and SmartPLS© software for modeling and graphing relationships among variables.Results: dependency, inequalities, innovation, and public policies largely explain the upgrading potential of producers of blackberry fruit in the global value chain. To the extent that these social actors can reduce dependency level and inequality; while innovation and public policies to support their production activities are developed,Limitations/ Implications of the study: there is no official record of blackberry fruit producers. The internal level of organization did not present a positive association with the economic upgrading of producers in the chain. However, it was positive in relation to external factors; it is important then to strengthen the individual positioning of each producer towards increasing productive capacity, as well as improving skills on marketing and sales of the product.Findings/ Conclusions: reduction in inequality and level of dependency that producers experience compared to the rest of the value chain, as well as innovation are the variables that positively impact economic upgrading of blackberry fruit producers in the municipality.